Development of ammonia gas leakage detection, precaution and purging system - Cheang, Chi Qing (2022)
The purpose of this project is to improve the existing observation methods for ammonia leaks to avoid accidents caused by the inhalation of excess ammonia. The leakage of ammonia gas is very dangerous and harmful to humans because it is corrosive (high concentration) and might cause burning to our face and somehow will direct cause death [1]. This project will improve unrelated measurement methods, which are fixed or mounted on walls, limiting the purpose of measuring only. The project incorporates Internet of Things technology to help monitor gas sensor readings (MQ-135) from a safe distance, locate areas or parts where ammonia gas is leaking based on pressure sensor readings, and include a precaution system (siren alarm & red and green LEDs) that acts as feedback and purging system that controls water pumps and fans as well as the solenoid valves to control ammonia gas inlet. It also has a GPS system that will pinpoint the location of any gas leakage. The project system focuses on the transfer of data from the sensing unit to the broker, where it is temporarily saved in the Blynk app, but can be stored for a long time and exported in the web ThingSpeak. The data is shown on a mobile and web application that allows users to monitor sensor readings. The data is sent to Blynk applications and the ThingSpeak protocol web via the NodeMCU, which reads data from inputs and outputs. The findings of the prototype testing revealed a working Blynk and ThingSpeak web application, with the metre providing precise latitude and longitude readings and the GPS system providing accurate latitude and longitude. This ammonia gas leakage detection and monitoring system has been created and tested satisfactorily. There are some recommendations for this project of ammonia gas leakage detection and monitoring system, including changing the gas sensor to MQ-137 because the MQ-135 is an air quality sensor and not a fully ammonia gas sensor, and switching to a different platform for web application monitoring that has a low data transfer delay.